Implementation and evaluation of communication guidelines for the nurses caring for patients diagnosed with tuberculosis - Kamenye, Esther; Iipinge, Scholastika; Van Dyk, Agnes (International Journal of Health, 2017)
This article focuses on the process of the implementation and evaluation of the guidelines on communication to enhance the communication skills of the nurses who are caring for the patients diagnosed with tuberculosis. This article consists of two sections. The first section deals with the implementation of the communication guidelines and the second section evaluates the implementation and the outcomes of the evaluation of the guidelines. The guideline's document was completed during a two-day training workshop held at the Katutura Health Centre in Namibia.